FORMATION OF READYNESS OF FUTURE MUSIC TEACHERS FOR THE DEVELOPMENT OF CREATIVE ABILITIES STUDENTS IN THE PROCESS OF INDIVIDUAL CLASSES (Pedagogy of Higher and Secondary Education, 2002)
In this article, we analyze the notions of “creativity”, “abilities" and “aptitudes Their theoretical parameters support the detailed study of certain aspects of future music teachers' training in terms of the development of creative abilities in their pupils. It is proved them the professional training of a specialist is more effective during individual classes.